The Effect of Chicken Bones Powder Adsorbent Mass and its Contact Time on Reducing Color Concentration in Peat Water Treatment - Leila Kalsum; Abu Hasan; Jordan Hasan; Selly Ratna Sari (Postgraduate, University of Mataram, 2024)
Peat water is surface water or ground water which is found abundantly in tidal, swampy and lowland areas. It has a reddish-brown color, with an acerbic taste (high acidity), and has a high organic content. Peat water can be treated using the adsorption method. Adsorption is a physical phenomenon in which the molecules of the adsorbed material are attracted to a solid surface, which acts as an adsorbent. In this study, the authors used the adsorption method to reduce the color concentration of peat water using activated chicken bones powder as an adsorbent and observing the changes that occur when mass of powder to the amount of 0.1, 0.2, 0.3, 0.4, 0.5, 1.0, 1.5 and 2.0 grams were added to 50 ml of peat water with contact time that varied from 20, 30, 40, 50 and 60 minutes. From this study, we conclude that the optimum yield was obtained when the mass and contact time were at 0.5 grams and 40 minutes, which yield a percentage of reduction of 95.59%, wherein the initial color concentration of peat water at 337.816 was reduced to 14.89 Pt-Co, which is in line with the standard color for clean water as specified in a Regulation by the Minister of Health of the Republic of Indonesia No. 492/MENKES/PER/IV/2010, which state the standard color for clean water is 15 Pt-Co.